Spexin and nesfatin-1-expressing neurons in the male human claustrum - Pałasz, Artur; Lipiec-Borowicz, Anna; Suszka-Świtek, Aleksandra; Kistowska, Julia; Horká, Petra; Kaśkosz, Andrzej; Piwowarczyk-Nowak, Aneta; Worthington, John J; Mordecka-Chamera, Kinga (Journal of chemical neuroanatomy, 2024)
Neuropeptides are involved in numerous brain activities being responsible for a wide spectrum of higher mental functions. The purpose of this concise, structural and qualitative investigation was to map the possible immunoreactivity of the novel regulatory peptides: spexin (SPX) and nesfatin-1 within the human claustrum. SPX is a newly identified peptide, a natural ligand for the galanin receptors (GALR) 2/3, with no molecular structure similarities to currently known regulatory factors. SPX seems to have multiple physiological functions, with an involvement in reproduction and food-intake regulation recently revealed in animal studies. Nesfatin-1, a second pleiotropic neuropeptide, which is a derivative of the nucleobindin-2 (NUCB-2) protein, is characterized by a wide distribution in the brain. Nesfatin-1 is a substance with a strong anorexigenic effect, playing an important role in the neuronal circuits of the hypothalamus that regulate food intake and energy homeostasis. On the other hand, nesfatin-1 may be involved in several important brain functions such as sleep, reproductive behaviour, cognitive processes, stress responses and anxiety. For the first time we detected and described a population of nesfatin-1 and SPX expressing neurons in the human claustrum using immunohistochemical and fluorescent methods. The study presents the novel identification of SPX and nesfatin-1 immunopositive neurons in the human claustrum and their assemblies show similar patterns of distribution in the whole structure.
Keywords: Animals; Nesfatin-1; Nucleobindins; lidé; Claustrum; neurony; Spexin; proteiny nervové tkáně; nukleobindiny; Humans; Neurons; proteiny vázající vápník; Male; Nerve Tissue Proteins; Brain; Neuropeptides; neuropeptidy; mužské pohlaví; zvířata; klaustrum; Calcium-Binding Proteins